Highly diastereoselective arylations of substituted piperidines - Seel, Stephanie; Thaler, Tobias; Takatsu, Keishi; Zhang, Cong; Zipse, Hendrik; Straub, Bernd Franz; Mayer, Peter; Knochel, Paul (Journal of the American Chemical Society, 2011)
A highly diastereoselective methodology for the preparation of various substituted piperidines via Negishi cross-couplings with (hetero)aryl iodides was developed. Depending on the position of the C−Zn bond relative to the nitrogen (position 2 vs position 4), the stereoselectivity of the coupling can be directed toward either the trans- or cis-2,4-disubstituted products. Density functional theory calculations on the relative stabilities of the Zn and Pd intermediates were performed to explain the high diastereoselectivities obtained. A novel 1,2-migration of Pd further expands this method to the stereoselective preparation of 5-aryl-2,5-disubstituted piperidines.
Gesehen am 31.10.2022